Predictors of sexual function among men after myocardial infarction: a pilot study. (2nd December 2021) - Smith, Asa B; Barton, Debra L; Jackson, Elizabeth A; Wittmann, Daniela; Smith, Jacqui; Davis, Matthew
Abstract : Background/Aims: Sexual dysfunction often persists among men who have had a myocardial infarction. While some cross-sectional and longitudinal research has been conducted, there are still no known modifiable targets for intervention. This pilot study aimed to model hypothesised predictive factors of higher sexual function in a cohort of men post myocardial infarction. Methods: Using a longitudinal study design, data on sexual function, sexual fear, anxiety and depressive symptoms, and use of coping strategies were collected using the Male Sexual Function Index, Multidimensional Sexuality Questionnaire, Patient-Reported Outcomes Measurement Information System and Coping Strategy Indicator respectively. Spearman correlations were estimated to examine associations between factors at 2 weeks and 3 months following myocardial infarction. Linear regression models were conducted for sexual function while controlling for age. Results: The data for 14 men were analysed. Sexual fear and use of problem-solving and support-seeking coping strategies were moderately correlated with sexual function at 3 months post myocardial infarction. Increased use of problem-solving and support-seeking coping strategies was associated with increased sexual function at 3 months. Conclusions: Use of coping strategies may predict increased sexual function 3 months post myocardial infarction. However, additional studies are needed to further examine these hypothesised relationships with a larger and more diverse sample.